Livestock Ownership and Children's Intakes of Animal Source Foods in Nepal (P10-057-19). (13th June 2019) - Broaddus-Shea, Elena; Manohar, Swetha; Thorne-Lyman, Andrew; Nonyane, Bareng A.S; Winch, Peter; Shrestha, Binod; West, Keith P
Abstract: Objectives: Animal source foods (ASF) promote young children's growth and development yet remain infrequently consumed in rural Nepal. Currently, agriculture and nutrition programs aim to increase ASF intake among children through small-scale animal husbandry projects. Yet the relationship between animal production and children's consumption of ASF is not well established. This study examined associations between poultry, cattle, and meat animal ownership and frequencies with which children eat eggs, dairy products, and meat, respectively. Methods: Longitudinal data from the Policy and Science of Health, Agriculture and Nutrition (PoSHAN) study's sentinel surveillance sites were used for this analysis. Using 7-day food frequency questionnaire data from 1449 surveys conducted twice per year for two years with 485 Nepali farming households, we determined whether number of cattle, poultry, and meat animals owned was associated with children's weekly dairy, egg, and meat intakes, respectively, while adjusting for household expenditure on each food type, mother's education level, caste/ethnicity, agroecological region, season, and child age and gender, employing negative binomial regression analysis. Results: Children consumed dairy 1.4 (95% CI 1.1–2.0), 2.3 (1.7–3.0) and 3.0 (2.1–4.2) more times per week in households owning 1, 2–4 and >4 cattle, respectively, compared to children in households with no cattle. Children consumed eggs 2.8 (2.1–3.7) more times per week in households owning 1 or 2 chickens compared to children in households without chickens. Owning more than 2 chickens was not associated with a significant additional increase in consumption. Child intake of meat only increased significantly in households with the highest levels of meat animal ownership (those owning 7 or more meat animals). Increased expenditure was significantly associated with increased consumption for all three food types. Conclusions: Findings are consistent with and support strategies that promote small-scale animal production as a potentially effective strategy for increasing children's consumption of eggs and dairy, but not of meat. Enabling households to increase expenditure on ASF is an important pathway for increasing children's consumption of all three food types. Funding Sources: Study funded by USAID via a subaward from Tufts University under the Feed the Future Innovation Lab for Nutrition. Additional assistance received from Sight and Life and the Gates Foundation.